The Dynamics of the Executive and Legislative Relations in the Indonesian Constitutional System - Hendrikus Haipon; Hamzah Mardiansyah; Muslimah; Herwantono; Moh. Siswanto (Universitas Muhammadiyah Palu, 2025)
This study explores the dynamic relationship between the executive and legislative branches within Indonesia’s constitutional system. Although formally based on the principle of separation of powers, the Indonesian political landscape is characterized by interdependence, negotiation, and compromise between the President and the House of Representatives (DPR). Through a qualitative approach using literature review and document analysis, the research highlights how coalition politics, oversight mechanisms, and political conflicts shape the nature of executive-legislative relations. Findings suggest that while theoretical models advocate institutional independence, practical governance in Indonesia relies heavily on collaboration and mutual adjustment. The study also discusses the implications of this interdependence for democratic accountability, policy-making efficiency, and institutional resilience. Ultimately, it argues that strengthening democratic institutions and encouraging political dialogue are essential for maintaining effective governance in a diverse and decentralized society like Indonesia.